2013
DOI: 10.1074/mcp.m112.024802
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomics Identified Novel Activation of Dynein IC2-GR-COX-1 Signaling in Neurofibromatosis Type I (NF1) Disease Model Cells

Abstract: Neurofibromatosis type 1 (NF1) tumor suppressor gene product, neurofibromin, functions in part as a Ras-GAP, and though its loss is implicated in the neuronal abnormality of NF1 patients, its precise cellular function remains unclear. To study the molecular mechanism of NF1 pathogenesis, we prepared NF1 gene knockdown (KD) PC12 cells, as a NF1 disease model, and analyzed their molecular (gene and protein) expression profiles with a unique integrated proteomics approach, comprising iTRAQ, 2D-DIGE, and DNA micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Here, we report the up-regulation of TCTP in neurofibromin-deficient PC12 cells and Schwann cells and its regulation of cellular viability. Interestingly, our proteomic data also revealed that eEF1A and eEF1B␤ were up-regulated in neurofibromin-deficient PC12 cells after NGF stimulation (6). Because major components of the translational machinery are frequently up-regulated in human tumors, including neurofibromatosis-associated tumors (17), it is reasonable to assume that the up-regulation of both TCTP and eEF1A/B␤ contributes to the hyperactivation of protein synthesis in neurofibromas.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Here, we report the up-regulation of TCTP in neurofibromin-deficient PC12 cells and Schwann cells and its regulation of cellular viability. Interestingly, our proteomic data also revealed that eEF1A and eEF1B␤ were up-regulated in neurofibromin-deficient PC12 cells after NGF stimulation (6). Because major components of the translational machinery are frequently up-regulated in human tumors, including neurofibromatosis-associated tumors (17), it is reasonable to assume that the up-regulation of both TCTP and eEF1A/B␤ contributes to the hyperactivation of protein synthesis in neurofibromas.…”
Section: Discussionmentioning
confidence: 62%
“…In our previous studies, using an integrated proteomics approach in neurofibromin-deficient PC12 cells (6), translationally controlled tumor protein (TCTP) was identified as an antiapoptotic factor uniquely regulated in response to NGF stimulation in PC12 cells (7). TCTP has been found in many eukaryotes, reported as multifunctional, and implicated in diverse processes, including growth, apoptosis, survival, development, protein synthesis, and transcription regulation (8).…”
Section: Neurofibromatosis Type 1 (Nf1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pathway Analysis-The statistical extraction of canonical pathways was conducted through the use of KeyMolnet (KM Data, Tokyo, Japan) (28). The list of the regulated phosphoproteins was imported into KeyMolnet and the "Interrelation search" algorithm was used to generate the network of the molecular interactions between the related proteins.…”
Section: Methodsmentioning
confidence: 99%
“…In neuroproteomics, these approaches have been extensively used to characterize the differential proteomes of neuronal disorders, drug responses or brain regions. Many studies have been performed using these techniques in areas such as neurodegenerative disorders, as the study of the putamen proteome of an MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) monkey model of Parkinson's disease [101] or in the serum of Parkinson's disease patients [102], or even in the analysis of synaptossomes from cortical brain tissues from Alzheimer's disease patients [103]; in neuropharmacoproteomics, as in the examples of a study of protein quantitative alterations induced by antidepressants in the hippocampus of mice [104]; also in addiction as in the evaluation of the effects of administration of plasminogen activator after ischemic injury in mice [105] or the alterations upon chronic exposure to cocaine [106]; in neuropsychiatric and other CNS disorders, such as schizophrenia, with the study of protein expression in the thalamus and CSF of patients [107] and a study of neurofibromin knockdown PC12 cell line as a model of neurofibrimatosis [108]; or even in studies of neuronal function such as memory formation in hippocampus [109].…”
Section: Chemical Labeling Approaches: Isobaric Techniquesmentioning
confidence: 99%